Fabrication of Oxide Ceramic MgFe2O4 Using Iron Oxide Isolated from Lapindo Mud as a Raw Material - Riska Yudhistia Asworo; Rachmat Triandi Tjahjanto; Akhmad Sabarudin (The Journal of Pure and Applied Chemistry Research, 2013)
The quite high content (28.8%) of iron oxide (Fe2O3) in Lapindo Sidoarjo`s mud promotes as a potential raw material for fabrication of oxide ceramics. The preeminence magnetic properties of iron oxide materials have led to be widely used for preparation of noteworthy products i.e semiconductor ceramics. However, the high band gap of iron oxide results in high resistivity, limiting its application as semiconductor ceramics. The addition of other oxides to iron oxide is able to reduce the energy gap of resulted oxide ceramics. Accordingly, in this study, MgO is added to Fe2O3 isolated from Lapindo mud for preparation of the oxide ceramic MgFe2O4. The products are characterized, which include crystal structure, crystal size and resistivity. It was found that the addition of MgO decreased the volume fraction of spinel structure formation, the average of crystal size, and the resistance value. The ratio MgO/Fe2O3 of 3:7 and a sintering temperature of 1300oC show the optimum composition for fabrication of MgFe2O4 with the volume fraction of 0.72 and the crystal size of 49.06 nm as characterized by XRD.